EVALUATION OF DISASTER RISK MANAGEMENT GOVERNANCE AT DISTRICT AND INTERMUNICIPAL LEVELS IN METROPOLITAN LIMA, PERU. 2025 - Sandoval, Jorge Lescano; Sena, Lucia Emperatriz Valdéz; Veja, Marlitt Florinda Naupay; Lobo, Manuel Rimarachin; Limazca, José Manuel Ramírez; Faura, Illary Elena Palacios (Veredas do Direito, 2026)
Metropolitan Lima, with 43 districts and a population of 13 million as of 2025, is the country’s main urban center and is exposed to both natural and human-induced hazards. The complexity of its territorial structure and the informal nature of its urban expansion make it necessary to improve disaster risk management (DRM) governance at the district and inter-municipal levels. The objective of this research was to evaluate DRM governance in the district municipalities and Metropolitan Lima, with an emphasis on policies, management systems, specific plans, and institutional capacities. Data were obtained from 43 districts and seven municipal associations in the Lima Metropolitan Area. The results reveal a high degree of dispersion among organizational units, weak standardization of plans, limited updating of management tools, and a low level of technical expertise in DRM. Only one association of municipalities has a Disaster Risk Prevention and Reduction Plan. The connection between territorial administration, sustainable urban growth, environmental management, climate change, and DRR is in its infancy. It is concluded that DRR governance in Metropolitan Lima is fragile, fragmented, and lacks sufficient intergovernmental and intersectoral coordination.